Pelaksanaan Kontrak Konstruksi Antara Dinas Pekerjaan Umum Dan Penataan Ruang (Pupr) Provinsi Nusa Tenggara Barat Dan Pt. Bunga Raya Lestari Dalam Pembangunan/Rehabilitasi Jalan Dan Jembatan Wilayah Sumbawa I - Delviana Aurellia Rieswandhani; Shinta Andriyani (Fakultas Hukum Universitas Mataram, 2022)
This research aims to find out the implementation and the obstacles that occur in the implementation of construction contracts between the Office of Public Works and Housing of West Nusa Tenggara Province and PT. Bunga Raya Lestari in the construction/rehabilitation of roads and bridges in region Sumbawa I. This is an empirical legal research by observing field data as the main source of research. Construction services activities require a form of written engagement between service providers and users of construction services called construction work contracts. A construction work contract is an important document that contains provisions that affect the rights and obligations for service users and service providers that are made in detail and must be look at all aspects, especially the legal aspects. Construction contract made between the Office of Public Works and Housing (PUPR) of West Nusa Tenggara Province and PT. Bunga Raya Lestari to carry out the construction/rehabilitation of roads and bridges in the region Sumbawa I, made legally and applicable as a law for those who make it. The contract phase is divided into three, namely the pre-contract, the contract and the post-contract. This road and bridge construction/rehabilitation activity is also inseparable from the obstacles that occur, such as non-technical obstacles and technical obstacles.